Structured follow-up by general practitioners after deliberate self-poisoning: a randomised controlled trial. Issue 1 (December 2015) - Grimholt, TK; Jacobsen, D.; Haavet, OR; Sandvik, L.; Jorgensen, T.; Norheim, AB; Ekeberg, O.
Abstract Background General Practitioners (GPs) play an important role in the follow-up of patients after deliberate self-poisoning (DSP). The aim was to examine whether structured follow-up by GPs increased the content of, adherence to, and satisfaction with treatment after discharge from emergency departments. Methods This was a multicentre, randomised trial with blinded assignment. Five emergency departments and general practices in the catchment area participated. 202 patients discharged from emergency departments after DSP were assigned. The intervention was structured follow-up by the GP over a 6-month period with a minimum of five consultations, accompanied by written guidelines for the GPs with suggestions for motivating patients to follow treatment, assessing personal problems and suicidal ideation, and availability in the case of suicidal crisis. Outcome measures were data retrieved from the Register for the control and payment of reimbursements to health service providers (KUHR) and by questionnaires mailed to patients and GPs. After 3 and 6 months, the frequency and content of GP contact, and adherence to GP consultations and treatment in general were registered. Satisfaction with general treatment received and with the GP was measured by the EUROPEP scale. Results Patients in the intervention group received significantly more consultations than the control group (mean 6.7 vs. 4.5 (p  = 0.004)). The intervention group was significantly more satisfied with the time their GP took to listen to their personal problems (93.1 % vs. 59.4 % (p  = 0.002)) and with the fact that the GP included them in medical decisions (87.5 % vs. 54. 8 % (p  = 0.009)). The intervention group was significantly more satisfied with the treatment in general than the control group (79 % vs. 51 % (p  = 0.026)). Conclusions Guidelines and structured, enhanced follow-up by the GP after the discharge of the DSP patient increased the number of consultations and satisfaction with aftercare in general practice. Consistently with previous research, there is still a need for interventional studies. Trial registration ClinicalTrials.gov Identifier:NCT01342809 . Registered 18 April 2011.